Concepção de oralidade: a teoria nos PCN e no PNDL X a prática nos livros didáticos - Magalhães, Tânia Guedes (2007)
This work is firstly aimed at investigating and analyzing the concept of oral skills as developed by the PCNs (National Curriculum Guidelines) and by the PNLD/2005 (National Programme of SchoolTextbooks), the latter being supported by MEC (Ministry of Education and Culture) as regards the choice of public school textbooks which are sponsored by federal financial resources. Secondly, bearing in mind that oral skills are supposed to be developed in the schools, two teaching manuals appointed by the PNLD/2005 Guide have been examined in order to verify if they offer activities which comprise the development of oral skills in the classroom. The data, which in this case imply the exercises proposed and their further analysis , show 1) a difference between the two documents (the PCN version and the PNLD/2005 Guide) concerning the very concept of oral skills and 2) a continuity of the dominance of written skills in the school, which reflects what is still going on in society, as opposed to the requirements found to be vital to the development of the students´oral skills. It is important to note that the interest in such subject was raised when the teachers who adopted these textbooks were heard. The concept of oral skills is aligned to the theoretical objectives of PCNs, the theoretical-practical tenets of the PNLD/2005 guide, the key teaching support for the Portuguese classes and the thoughts and opinions of the professionals to whom the documents are geared and who experience the dichotomy between oral and written skills in their everyday school context.